Mean reticulocyte volume: a specific parameter to screen for hereditary spherocytosis. (6th May 2015) - Xu, Yuchan; Yang, Wang; Liao, Lin; Deng, Zengfu; Qiu, Yuling; Chen, Wenqiang; Lin, Faquan
Abstract: This study assessed the value of mean reticulocyte volume (MRV) for differential diagnosis of hereditary spherocytosis (HS) so as to develop conventional and new specific screen indexes. Subjects in this study were divided into three groups: 53 cases in HS group, 217 cases in hemolytic anemia control group (109 cases of thalassemia (THAL), 56 cases of glucose‐6‐phosphate dehydrogenase G6PD deficiency anemia, and 52 cases of autoimmune hemolytic anemia (AIHA)), and 100 cases in healthy control group. We analyzed erythrocyte and reticulocyte parameters including MRV, mean sphered corpuscular volume, mean corpuscular hemoglobin concentration, and immature reticulocyte fraction. Results demonstrated that MRV was significantly lower in the HS group but significantly higher in the AIHA and G6PD deficiency anemia groups than that in the healthy control group ( P = 0.000). MRV was not significantly different between the AIHA and G6PD deficiency anemia groups ( P = 0.977) and between the healthy control and THAL groups ( P = 0.168). The area under the ROC curve of MRV for diagnosis of HS was 0.942, with a standard error of 0.019, 95% confidence interval of 0.905–0.979, and optimal critical diagnosis point of 95.77 fL. When the MRV was ≤95.77 fL, the sensitivity and specificity for diagnosis of HS were 86.80% and 91.20%, respectively. Therefore, MRV is a general and specific new index for screening HS and important for differential diagnosis of different types of hemolytic anemia.